Improving the productivity and income of Ghanaian cocoa farmers while maintaining environmental services: what role for certification? - Gockowski, J.; Afari-Sefa, Victor; Sarpong, D.B.; Osei-Asare, Y.B.; Agyeman, N.F. (Informa UK Limited, 2013)
Ghana, as the second largest global producer of cocoa, is strategically positioned on the world market. Consumer concerns over ethical and environmental issues associated with cocoa production are a potential threat to its position. These concerns have given rise to certification. Certification dictates the way cocoa can be produced and consequently affects producers’ incomes and environmental services. The expected profitability, yield, and environmental impact of Rainforest Alliance certified shade-grown cocoa production (RA-Cocoa) is estimated and compared to an extensive shaded production system (Ext-Cocoa) and an intensified full sun production system (High-Tech). Ext-Cocoa represents most cocoa production systems in Ghana, while High-Tech is promoted by the government as a tool for attaining its target output of 1 million tons. Under the baseline assumptions High-Tech was the most profitable; RA-Cocoa generated positive returns, while Ext-cocoa was a break even proposition. Simulation of different policy scenarios did not affect the rank order of the baseline outcome. The Ext-Cocoa yield was 28% of the RA-Cocoa yield, which was 78% of the High-Tech yield. The environmental services maintained at the plot level of RA-Cocoa production system are greater than those of the High-Tech production system. However, the 228,000 ha of additional forest land required to produce 1 million tons with RA-Cocoa questions which system would impact environmental services the least.